The Analysis of Factors Influencing Organizational Culture Success at Social Security Administrative Body for Health - Prasetyo, Rizky Fajar; Siswandi, Siswandi; Gadistina, Welly; wibhawa, harie; Kumalasari, Anggraeny; Syahputra Gani, Muhammad Yusuf; Nugraha, M. Satria; Arma, Sylvia; Ramadhan, Aditya (Jurnal Jaminan Kesehatan Nasional, 2025)
Organizational culture serves as the foundation for institutional behavior and performance. Employees’ perceptions of cultural success play a critical role in ensuring the effective implementation of core values. This study aims to analyze the factors associated with perceptions of organizational culture success at BPJS Kesehatan, using the INITIATIVE framework (Integrity, Collaboration, Excellent Service, and Innovation). A quantitative approach with a descriptive-analytical survey design was employed. Data was collected from 236 respondents using validated questionnaires and analyzed through Pearson correlation and multiple linear regression. The findings indicate that leadership role modeling, contextual value internalization, and system consistency are significantly associated with perceptions of cultural success. Other variables, such as change agents, communication, and structural support, show a positive but statistically insignificant association. These results provide practical recommendations to strengthen leadership, internalize values, and align systems to sustain an effective organizational culture in public service institutions